An Implementation of Location Based Service (LBS) for Community Tracking - Yulianto, Budi; Layona, Rita (Bina Nusantara University, 2017)
The case of lost or missing children when people go traveling or in the hustle often occurs due to lack of parental supervision. These problems can be solved using Global Position System (GPS)-based navigation technology Location Based Service (LBS). This research aimed to determine the position of members of the community (such as family) who were lost or missing by using mobile devices. Rapid Application Development (RAD) was used for system development, which comprised the step of requirement or planning, system design, development, and cutover. The result of this research is a GPS-based application that is able to display the position of members of the community, the route to the location, and the media discussion (comments). The conclusions show that the application provides an easy and useful function in finding the location of the community member, displays the route to the location, and allows the interaction in the form of communication.